Hubungan Citra Tubuh, Pola Konsumsi dan Aktivitas Fisik dengan Status Gizi Siswi SMA di Kota Ende - Agustina Salsa Badhe Bata; Sarci Magdalena Toy; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
During During adolescence, major changes occur in terms of body growth and development. Physical growth and development in adolescents increases nutritional needs. Nutritional problems often occur during adolescence. Status where nutrients are needed by the body as a source of energy, growth and maintenance of body tissue and regulator of body processes. Body image, consumption patterns and physical activity can influence the nutritional status of adolescent girls. The aim of this research is to determine the relationship between body image, consumption patterns and physical activity on the nutritional status of female students in Ende City. This type of research is analytical observational with a cross sectional design, a probability sampling technique of 220 people. The results of this research show that there is a relationship between body image and the level of protein consumption (p=0.023) and OR = 1.962, the level of energy consumption (p=0.00) and OR = 35.444, the level of fat consumption (p=0.03) and OR = 1.882 and the level of carbohydrate consumption (p = 0.00) and OR = 5.673 on the nutritional status of female students at SMA Negeri 1 Ende, meanwhile, body image with the level of energy consumption (p = 0640), the level of fat consumption (p = 0.363), the level of Carbohydrate consumption (p=0.451) showed no relationship. The level of protein consumption (p=0.114) and physical activity (p=0.809) also had no relationship to the nutritional status of female students at SMA Negeri 1 Ende. There is a need for nutritional education, monitoring of nutritional status in schools, as well as the need for education for female students to pay more attention to the food they consume.